The Effects of Alcohol and Sexual Arousal on Determinants of Sexual Risk in Men Who Have Sex with Men - Maisto, Stephen A (2011)
Primary prevention efforts aimed at sexual risk behaviors are critical. This experiment was designed to investigate the effects of alcohol intoxication and sexual arousal, as well as person variables of alcohol sex expectancies and attitudes toward condom use, on hypothesized determinants of sexual risk behaviors among men who have sex with men (MSM). The participants were 117 MSM aged 21–50 years who were randomly assigned to one of six separate experimental conditions created by the combination of beverage administration (water control, placebo or alcohol designed to raise blood alcohol level to .07%) and sexual arousal (low or high, manipulated by participants’ viewing non-erotic or mildly erotic film clips). Participants attended two experimental sessions. The first session included completing questionnaires about beliefs about alcohol’s effects on sex and attitudes toward condoms’ effect on sexual pleasure. The second session involved the beverage condition and arousal manipulations. Following these, participants viewed and responded to two interactive videos depicting high sexual risk scenarios. Participants also completed the CARE, a measure of risk perceptions. The dependent variables were behavioral skills, intentions to have unsafe sex, and “risk exposure,” derived from responses to the videos. The results of both planned and exploratory analyses showed general support for the hypothesized enhancement of alcohol’s effects on sexual risk by both sexual arousal and expectancies. Also as predicted, condom attitudes showed direct relationships to risk exposure and intentions. Implications of the findings for models of alcohol’s effects on sexual risk and for the development of HIV prevention interventions were discussed.